(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2007)
In suspected drowning cases forensic pathologists are often asked whether the drowning was anti-mortem or post-mortem, and along with this an equally important question to be answered here is that if the death really took place at the same site from where the body was recovered. Here question arises about the exact site of drowning and in forensic investigations; it imparts necessity for the precise localization of site of drowning. The proposed study deals with the algological analysis that, in turn has recorded diatom type in three water bodies of Jaipur (Rajasthan) region. On the basis of this database, diatomological maps have been designed, which are supposed to be of immense help in diagnosis of suspected drowning cases occurring in this region.